Implikasi Yuridis Perubahan PT. ASKES (Persero) Menjadi BPJS Kesehatan - Djumardin Djumardin (Faculty of Law, Universitas Wijayakusuma, 2020)
Implementation of social security is a state obligation mandated by the 1945 Constitution, with the issuance of the BPJS Law as the executor of the SJSN Law, resulting in PT. Askes (Persero) is fighting to become BPJS Kesehatan. For this reason, this research is intended to address the main legal issue, namely